Protecting Peer Support Values and Ethics Through Community-Engaged Bioethics - de Bie, Lee; Knopes, Julia; Dunning, Allison; Theodorou, Allyson; Fortier, Brookelyn (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
There has been a long history of cross-pollination between peer support (PS) in the United States and Canada, but collaboration has declined over the past two decades as PS has become increasingly professionalized. With government recognition and funding, PS has moved from informal friendships in the community among those with similar lived experiences towards paid PS employment in clinical services. In this commentary we argue that PS in Canada and the US should return to working together. We share ethical challenges related to the professionalization — and associated co-optation and drift — of PS, where PS deviates from its unique grounding in authentic human connection, social movement organizing, and core values of self-determination, shared power, hope, and mutuality. The resulting loss of the transformative power of PS is particularly potent in our current moment when it has so much to offer. We describe how our team of community-engaged bioethicists from Canada and the US and leaders of the PS discipline in Canada are collaborating to elaborate, legitimize, and protect the unique values and ethics of this expanding and evolving modality of care.